46th AIAA Aerospace Sciences Meeting and Exhibit 2008
DOI: 10.2514/6.2008-385
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Unsteady Flows around Dragonfly and Smooth Airfoils at Low Reynolds Numbers

Abstract: A computational study was conducted to investigate the unsteady quasi-two-dimensional flow around a streamlined NASA low-speed GA(W)-1 airfoil and a corrugated dragonfly airfoil at the Reynolds numbers of 68,000 and 55,000. Both 2D and 3D simulations were carried out by solving the unsteady Navier-Stokes equations to predict the behavior of the unsteady flow structures around the airfoils at different angles of attack (AOAs). Extensive comparisons were made between the numerical results and wind-tunnel experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…However, LES is compatible with a wider range of turbulent flows than RANS model, as it retains the unsteady large-scale coherent structures. For example, Cummings et al [19], Gao et al [21], and Li et al [29] proved that LES is an effective tool for simulating unsteady separated flows. The Smagorinsky-Lilly model overcomes the limitation of the original Smagorinsky sub-grid model and is one of the best-known LES models [30,31].…”
Section: Turbulence Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, LES is compatible with a wider range of turbulent flows than RANS model, as it retains the unsteady large-scale coherent structures. For example, Cummings et al [19], Gao et al [21], and Li et al [29] proved that LES is an effective tool for simulating unsteady separated flows. The Smagorinsky-Lilly model overcomes the limitation of the original Smagorinsky sub-grid model and is one of the best-known LES models [30,31].…”
Section: Turbulence Modelsmentioning
confidence: 99%
“…The spanwise length is not fully modeled in such a 3D simulation, so that it is referred to as 2.5D CFD simulation hereinafter in order to differentiate it from the conventional 2D and 3D simulations. Gao et al [21] performed 2.5D LES simulations of the flow field around a single static airfoil and found that the 2D model is not adequate for predicting unsteady flow structures with large-scale separations around airfoils at relatively high AOAs. Furthermore, Travin et al [22], Bertagnolio et al [23], and IM and Zha [24] presented simulations of a single airfoil beyond stall using the DES method, which is essentially a hybrid model of RANS and LES.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, LES turbulence models are suitable for a wider range of turbulent flows than RANS models. Cummings et al [44], Gao et al [45], and Li et al [46] have proved that LES turbulence models are rather effective in simulating unsteady separated flows. Meanwhile, Smagorinsky-Lilly model has conquered limitations of the original model, and become the best known LES model [47,48].…”
Section: Turbulence Models In Cfdmentioning
confidence: 97%
“…At certain tip-speed ratios (TSR) namely, λ ≥ 5, the angle of attack does not exceed 12 deg. Previous researchers [3][4][5] have found that three-dimensional large-eddy simulation (LES) [6] is necessary to accurately predict the lift and drag of a stalled airfoil. At the lowest TSR (λ ≤ 1), Li et al [5] showed that three-dimensional (3-D) LES [this form of LES is sometimes called (2.5-D) LES] could accurately predict the tangential force of a straight-bladed VAWT at Re 10 5 .…”
Section: Nomenclaturementioning
confidence: 99%